2016
DOI: 10.1007/s10865-016-9725-y
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia symptoms and heart rate recovery among patients in cardiac rehabilitation

Abstract: Insomnia symptoms (i.e., difficulty falling asleep, difficulty staying asleep, and early morning awakenings) are common among people with cardiovascular disease, and have been linked to adverse cardiovascular health outcomes. Reduced parasympathetic tone is one pathway through which risk may be conferred. The purpose of this study was to evaluate whether insomnia symptoms are associated with lower parasympathetic tone in cardiac rehabilitation patients with suspected insomnia. Participants (N = 121) completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…49 A recent cross-sectional study demonstrated an association between difficulty falling asleep and reduced parasympathetic tone (measured by 1-min heart rate recovery from maximal exercise test) in patients undergoing cardiac rehabilitation who had moderate to severe insomnia. 50 In this study, insomnia severity was ascertained using the Insomnia Severity Index, a wellvalidated 22,51 questionnaire commonly used to screen and grade insomnia. A study of > 500 participants in the Multiethnic Study of Atherosclerosis showed that participants who slept # 7 hours per night and reported insomniac symptoms had greater heart rate orthostatic reactivity and a high frequency of heart rate variability reactivity to mental stress than participants who slept > 7 hours per night with no insomniac symptoms.…”
Section: Insomnia and Cvd Pathophysiology: Underlying Mechanismsmentioning
confidence: 99%
“…49 A recent cross-sectional study demonstrated an association between difficulty falling asleep and reduced parasympathetic tone (measured by 1-min heart rate recovery from maximal exercise test) in patients undergoing cardiac rehabilitation who had moderate to severe insomnia. 50 In this study, insomnia severity was ascertained using the Insomnia Severity Index, a wellvalidated 22,51 questionnaire commonly used to screen and grade insomnia. A study of > 500 participants in the Multiethnic Study of Atherosclerosis showed that participants who slept # 7 hours per night and reported insomniac symptoms had greater heart rate orthostatic reactivity and a high frequency of heart rate variability reactivity to mental stress than participants who slept > 7 hours per night with no insomniac symptoms.…”
Section: Insomnia and Cvd Pathophysiology: Underlying Mechanismsmentioning
confidence: 99%
“…Current evidence indicates that autonomic nerve dysfunction is a potential mechanism of insomnia, and therefore, insomnia patients tend to have increased sympathetic and reduced parasympathetic tones [ 57 ]. In HRV, high-frequency power (HF) is attributed to parasympathetic nerve activity, while low-frequency power (LF) indicates functions related to sympathetic and vagal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence indicates that autonomic nerve dysfunction is a potential mechanism of insomnia, and therefore, insomnia patients tend to have increased sympathetic and reduced parasympathetic tones (57). In HRV, high-frequency power (HF) is attributed to parasympathetic nerve activity, while lowfrequency power (LF) indicates functions related to sympathetic and vagal nerves.…”
Section: Discussionmentioning
confidence: 99%